Prevalence of cholesterol gallstones in a Korean population over a 14-year period - Gyumin Lee; Jeong Yoon Suh; Junyeol Kim; Tae Young Park; Jae Hyuk Do; Yoo Shin Choi; Seung Eun Lee; Tae Yoon Lee; Hyun Kang; Hyoung-Chul Oh (The Korean Journal of Internal Medicine, 2025)
Background/Aims The incidence of cholesterol gallstones has increased in the last few decades. This study aimed to evaluate the prevalence of cholesterol gallstones in Korea over a 14-year period, analyze any changes, and identify the predisposing factors. Methods A total of 3,909 patients underwent cholecystectomy for gallstones over the 14-year period and were considered for inclusion in this study. Patients were divided into cholesterol and pigment gallstone groups based on gallstone composition, as determined by Fourier Transform Infrared spectroscopy. Patient characteristics were compared between the two groups. Results After the exclusion of 259 patients with mixed type gallstones, 3,650 patients were finally included in this study; 2,038 (55.8%) with cholesterol gallstones and 1,612 (44.2%) with pigment gallstones. The proportion of cholesterol gallstones over the 14-year period was 53.8% of the study population as a whole and 77.5% of individuals aged < 50 years. The multivariate analysis revealed that cholesterol gallstones were associated with an age < 50 years, female sex, central obesity, absence of chronic liver diseases, and diabetes mellitus. High density lipoprotein-cholesterol levels showed a tendency toward an association with cholesterol gallstones. Conclusions The prevalence of cholesterol gallstones in Korea plateaued 53.8% during the 14-year period. However, given the increasing incidence of cholesterol gallstones among younger individuals, the relative prevalence of cholesterol gallstones may increase in the future.